Análisis comparativo con la aplicación de un software educativo Euclides, en la resolución de sistemas de ecuaciones lineales, por la estrategia de eliminación y gráfica, en los estudiantes del décimo año de educación básica del colegio Dr. Camilo Gallegos Toledo, período septiembre 2015 – enero 2016 - Flores Escobar, Mayra Karina (2016)
The present study has the aim to analyze the academic performance of students in a comparative way with and without the application of an educational software called “Euclides” in the resolution of systems of lineal equations by using the strategy of elimination and graphic in the tenth year students of basic education at the “Camilo Gallegos Toledo” school, term September 2015-January 2016. The present study has a constructivist approach with a quantitative type of study and a quasi-experimental design, it is a descriptive, correlational and 72 students, with a sample of 61 students, compose field research, the population. The hypothetic-deductive method was applied. The study considered two groups, an experimental group (10th level students, class “A”) and the controlling group (10th level students, class “B”) whose a pretest was given and a post-test to determine their academic performance. With the experimental group a didactic guide was applied to solve the exercises with the assistance of this mathematical software called “Learning with Euclides”. Statistic and inferential processes in Excel and Geogebra carried out the statistical analysis. It can be observed a significant influence between the educational software called “Euclides” and the students´academic performance. Besides, in the experimental group when the pre-test was applied, the students’ academic performance reacheda score of 6,60 points. However, after the application of the pedagogical guide called “Learning with Euclides” the students´ academic performance reached a score of 7, 40 points, something that represents a meaningful progress.